2022
DOI: 10.3390/cancers14041093
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and Quality of Life among Patients with Cancer during the SARS-CoV-2 Pandemic: Results from the Longitudinal ONCOVID Survey Study

Abstract: Purpose: This longitudinal survey study aimed to investigate the self-reported outcome measures of COVID-19 peritraumatic distress, depression, anxiety, stress, quality of life (QOL), and their associated factors in a cohort of cancer patients treated at a tertiary care hospital during the SARS-CoV-2 pandemic. Methods: Surveys were administered at four time points between 1 April 2020 and 18 September 2020. The surveys included the CPDI, DASS-21, and WHOQOL-BREF questionnaires. Results: Survey response rates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 46 publications
4
33
1
1
Order By: Relevance
“…Similarly, recent findings reported poor QoL in earlier waves of the pandemic compared to late pandemic, indicating that adapting to changes in daily life has reduced the anticipated impact on Qol over time [ 37 ]. However, previous studies suggested that the QoL of populations during the COVID-19 pandemic does not differ over time [ 38 ]. Further research is needed to confirm the current and earlier findings.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, recent findings reported poor QoL in earlier waves of the pandemic compared to late pandemic, indicating that adapting to changes in daily life has reduced the anticipated impact on Qol over time [ 37 ]. However, previous studies suggested that the QoL of populations during the COVID-19 pandemic does not differ over time [ 38 ]. Further research is needed to confirm the current and earlier findings.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a prospective cohort study in 890 African American cancer survivors evaluated the impact of the pandemic on patient-reported health outcomes and 40% of participants reported feeling anxious, depressed, and/or isolated [33]. Lastly, several studies evaluating mental health during the pandemic in both cancer and non-cancer populations found no differences by race/ethnicity [5,20]. The difference in sex and age distributions across our study and cohorts from other studies may explain these con icting results.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the proportion of patients who reported experiencing sadness or depression was 30.7%, which was consistent with previous ndings. However, according to survey studies and literature review, the incidence of anxiety or depress among cancer patients in other western countries during COVID-19 pandemic was about 33.5% to 47% [14,21,22]. Although Chinese cancer patients might experience less psychological distress compared with patients from western countries, they still need more professional psychosocial support which has not been fully addressed.…”
Section: Discussionmentioning
confidence: 99%